Perlindungan Hukum atas Ekspresi Budaya Tradisional Indonesia dalam Sistem Hak Kekayaan Intelektual Berdasarkan Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta - Pebrianto, Pebrianto; Yossi Rizky Nanda; Rahmat Sholihin; Aiman Fiqri; Bima Saputra (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
Intellectual property rights now function not only to protect individual rights but also to regulate knowledge, culture, innovation, and benefit-sharing in the creative and digital economy era. In Indonesia, the protection of traditional knowledge and traditional cultural expressions has become increasingly important due to the high risk of misappropriation, unauthorized reproduction, and unfair commercialization. This article analyzes the legal protection issues concerning the intellectual property of indigenous and traditional communities and evaluates the adequacy of the existing national legal framework. The study shows that the current regulations remain fragmented across various legal instruments and have not yet formed a comprehensive protection system. Conventional IPR regimes are also not fully capable of accommodating the communal, intergenerational, spiritual, and social characteristics inherent in traditional cultural objects. Therefore, legal reform is needed toward a more substantive, participatory, and culturally just approach.